Increased monocyte and T-cell activation in treated HIV+ Ugandan children: associations with gut alteration and HIV factors. (1st June 2020) - Dirajlal-Fargo, Sahera; Albar, Zainab; Bowman, Emily; Labbato, Danielle; Sattar, Abdus; Karungi, Christine; Nazzinda, Rashida; Funderburg, Nicholas; Kityo, Cissy; Musiime, Victor; McComsey, Grace A.
Abstract : Introduction: The pathophysiology of immune activation and its mechanisms in children living with perinatally acquired HIV (PHIV) in sub-Saharan Africa has been understudied. Methods: We enrolled 101 children living with PHIV and 96 HIV-negative controls (HIV−). All participants were between 10 and 18 years of age with no known active infections. PHIVs were on ART with HIV-1 RNA level 400 copies/ml or less. We measured plasma and cellular markers of monocyte activation, T-cell activation (expression of CD38 + and HLA-DR on CD4 + and CD8 + ), oxidized lipids, markers of gut integrity and fungal translocation. Spearman correlations and linear regression models were used. Results: Overall median (Q1; Q3) age was 13 years (11; 15) and 52% were girls. Groups were similar by age, sex and BMI. Median ART duration was 10 years (8; 11). PHIVs had higher monocyte and T-cell activation; higher sCD14 ( P = 0.01) and elevated frequencies of nonclassical monocytes ( P < 0.001 for both). Markers of systemic inflammation (hsCRP), fungal translocation (BDG), intestinal permeability (zonulin) and oxidized lipids (ox LDL) correlated with monocyte and T-cell activation in PHIV (⩽0.05). After adjusting for age, sex, ART duration, protease inhibitor and nonnucleoside reverse transcriptase inhibitor use, a modest association between BDG and activated CD4 + T cells was observed ( β =0.65, P < 0.01). Oxidized LDL was inversely associated with activated T cells, inflammatory and nonclassical monocytes ( P < 0.01). Conclusion: Ugandan children with perinatally acquired HIV with viral suppression have evidence of ongoing immune activation. Intestinal barrier dysfunction and fungal translocation may be involved in chronic immune dysfunction.